VARIASI SPASIOTEMPORAL URBAN HEAT ISLAND DI KAWASAN PERKOTAAN YOGJAKARTA TAHUN 2015-2017 - Zahro, Haura; Sobirin, Sobirin; Wibowo, Adi (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2018)
The limitation of Yogyakarta City to meet the demand for impervious land make the development expands to Sleman and Bantul regency so that formed the Urban Area of Yogyakarta. This study aims to determine the pattern of surface temperature, its relationship with the vegetation greenness and the occurrence of the UHI phenomenon in the Urban Area of Yogyakarta in 2015- 2017. The surface temperature was obtained from Landsat 8 OLI / TIRS image processing by the mono-window method and validated by direct air temperature measurement, vegetation greenness with NDVI algorithm and UHI when the surface temperature above 30 ºC. The results show that the farther from the city center the surface temperature drops to 0.93ºC per kilometer. The highest surface temperatures occur in October 2015 and September 2017. The surface temperature has a strong correlation value with vegetation greenness with correlation coefficient up to -0.709 that is the higher the vegetation greenness the lower surface temperature. UHI phenomenon occurs every month with variation 11,85-4,01ºC and the highest surface UHI phenomenon occurs in October 2015with 41,85ºC. In conclusion, the UHI phenomenon occurs every month with the highest temperature and most intensive area of the UHI phenomenon is in October 2015.